Influence of Lubricants and Attrition Milling Parameters on the Quality of Zirconolite Ceramics, Consolidated by Hot Isostatic Pressing, for Immobilization of Plutonium. (20th February 2014) - Squire, Jonathan; Maddrell, Ewan R.; Hyatt, Neil C.; Stennett, Martin C.
Abstract : The effect of attrition milling on the processing of precursor oxides was investigated, with reference to the fabrication of titanate ceramics for the immobilization of plutonium and actinides, consolidated by hot isostatic pressing. Difficulties encountered during the lubricant removal step masked any correlation between the milling conditions and the final product. Four lubricants were investigated zinc stearate, Ceridust™, polyethylene glycol and oleic acid. The precursor blends were added to these lubricants to ensure the powders remained free flowing while dry milling in an attrition mill. All except Ceridust™ allowed the milled powders to be freely discharged. Examination of the products showed that each sample was highly porous and all were below the target minimum of 92 % of theoretical density. XRD and SEM analysis showed the production of a multiphase ceramic (zirconolite, perovskite, ilmenite) rather than the single target phase zirconolite. The impact of incomplete lubricant burn out on the oxidation states of Ce and Fe was investigated by XANES and Mössbauer spectroscopy, respectively. Suggested modifications to the HIP processing line, including the addition of an in situ sintered metal filter, the use of fumed metal oxides and the introduction of electrical conductivity in the precursors, are presented.